Characteristics of viral pneumonia in non-HIV immunocompromised and immunocompetent patients: a retrospective cohort study - Lijuan Li; Steven H. Hsu; Chunlei Wang; Binbin Li; Lingxiao Sun; Jinying Shi; Yali Ren; Jinxiang Wang; Xiaoqi Zhang; Jiangbo Liu (BMC Infectious Diseases, 2021)
Abstract Background Concerning viral pneumonia, few large-scale comparative studies have been published describing non-HIV immunocompromised and immunocompetent patients, but the epidemiological characteristics of different viruses or underlying diseases in immunocompromised hosts are lacking. Methods We retrospectively recruited patients hospitalised with viral pneumonia from six academic hospitals in China between August 2016 and December 2019. We measured the prevalence of comorbidities, coinfections, nosocomial infections, and in-hospital mortalities. Results Of the 806 patients, 370 were immunocompromised and 436 were immunocompetent. The disease severity and in-hospital mortality of immunocompromised patients were higher than those of immunocompetent patients. During the influenza season, an increased number of cases of influenza virus (IFV) infection were found in the immunocompromised group, followed by cases of cytomegalovirus (CMV) and respiratory syncytial virus (RSV) infection. During the non-influenza season, CMV was the main virus detected in the immunocompromised group, while RSV, adenovirus (AdV), parainfluenza virus (PIV), and rhinovirus (HRV) were the main viruses detected in the immunocompetent group. Pneumonia caused by Pneumocystis jirovecii (22.4%), Aspergillus spp. (14.1%), and bacteria (13.8%) were the most frequently observed coinfections in immunocompromised patients but not in immunocompetent patients (Aspergillus spp. [10.8%], bacteria [7.1%], and Mycoplasma spp. [5.3%]). CMV infection and infection with two-or-more viruses were associated with a higher in-hospital mortality rate than non-IFV infection. However, patients with IFV and non-IFV infection in immunocompromised patients had similar disease severity and prognosis. Conclusions Immunocompromised patients have a high frequency of coinfections, and a higher mortality rate was observed among those infected with CMV and two-or-more viruses. In addition, patients with IFV and non-IFV infection in immunocompromised patients had similar same disease severity and prognosis. The type of viral infection varied with seasons.